If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 4) = 36 Reorder the terms: 3(4 + 4x) = 36 (4 * 3 + 4x * 3) = 36 (12 + 12x) = 36 Solving 12 + 12x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12x = 36 + -12 Combine like terms: 12 + -12 = 0 0 + 12x = 36 + -12 12x = 36 + -12 Combine like terms: 36 + -12 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| f(x-5)=x^2+kx+30 | | x^2+18+c= | | 3x^3+14x-5=0 | | 144=12x+3 | | 180=(8x+5)+(3x+10) | | X^2+Y^2-2x+4y=20 | | M-5=28 | | -2x^2+5x=-18 | | x^2-39=-10x | | 13=2p+4p-11 | | (6i-2+x)(-6i-2+x)= | | 2+3x-5(x-3)=6x+1 | | 20-y=-14 | | P=-5x^2+50x+1000 | | 9+8lnx=12 | | x^2(x-32)=0 | | 4(7x+7)=308 | | x^2-39=10x | | 10x+9x-5+47+90=360 | | 6(x-4)+5=6 | | y=(x^2-1)(3x^2-5x+1) | | 2+8i=0 | | -1.2m=3.4m | | 2x+17=6x-7 | | 2x+11y=23 | | -1.2m=4 | | 5x+7y=98 | | x^2+3x-10=8 | | 180=(3x+10)+(4x-8) | | 3b-15=17-b | | 5(x+7)-8(x+9)=99 | | 0.3x-1.2=3.9x+1.8 |